Glycoconjugations of Biomolecules by Chemical Methods - Sarkar, Biswajit; Jayaraman, Narayanaswamy (Frontiers in Chemistry, 2020)
Bioconjugation of carbohydrates under benign aqueous conditions has the most promise to covalently link carbohydrates onto chosen molecular and macromolecular scaffolds. Development of chemical synthetic routes holds key to achieve the objective of bioconjugation of sugars with reactive functionalities present in such scaffolds. Chemical methodologies relying on C-C and C-heteroatom bond formations are the methods of choice, coupled with the reaction conditions being under the aqueous milieu. A number of methods, including metal-mediated, as well as, metal-free azide-alkyne cyclo-addition, maleimide reaction, photocatalyzed thiol-ene reaction, amidation, reductive amination, disulfide bond formation, conjugate addition, nucleophilic addition to vinyl sulfones and vinyl sulfoxides, native chemical ligation, Staudinger ligation, olefin metathesis and Suzuki-Miyaura cross coupling reactions have been developed, in efforts to covalently link carbohydrate moieties onto chosen molecular and biomolecular structures. Within these, many methods require pre-functionalization of the scaffolds prior of glycoconjugation, whereas methods that do not require such pre-functionalization continue to be far and few. The compilation shall cover synthetic methodology development for carbohydrate conjugation onto biomolecular and biomacromolecular scaffolds. Importance of such glycoconjugations on the functional properties is also discussed.